The Causes of Use of the Dashboard in Early Warning System - Dudycz, Helena (Advanced Information Technologies for Management – AITM 2008, 2008)
Analysts and executives alike recognize the stumbling blocks of contemporary analytics: endless columns of data, inflexible charts, disparate reports and delayed information that impede timely decision making. The quick obtainment of critical business information is very significant problem. The aim of the following article is to analyze characteristics of dashboard as tool to support monitoring the key performance indicators in early warning system. The first part briefly characterizes early warning system. The next part describes characteristics of information visualization to show business information. The last part of this article contains analysis of dashboard as technological solution facilitating identifying chances of advancement and threats of the establishment bankruptcy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 58-66